Contract law in the construction industry context - Circo, Carl J., 1949- (Spon research., 2020)
"This book chronicles how contract cases from the construction industry have influenced, solidified, refined and particularized U.S. contract law. The book's central claim is that the construction industry experience has helped to contextualize U.S. contract law and, therefore, has encouraged the common law to be more receptive to flexible legal standards and practices and less constrained by the relatively rigid rules that often characterize contract law. Other scholarly books analyze the themes, values, standards, and principles of contemporary contract law, but none capture how construction industry relationships and practices have influenced the common law of contracts. After providing an overview of construction law as a specialty of the practicing bar and as a field for scholarly inquiry, this book examines the construction industry cases that have most directly influenced contract law. It reviews how industry dispute patterns have caused courts to refine contract law principles or to adapt and modify other principles. Separate chapters explain the special roles that cases in the U.S. Supreme Court and in the lower federal courts have played in defining and distinguishing contract law in the construction industry. The final chapters assess implications the construction industry cases hold for contract theory writ large and for the future of contract law. This book is essential reading for legal scholars, construction law and contract law specialists, and those interested in how the construction industry has helped shape the U.S. legal system"--